DEVELOPING ENGLISH LESSON PLAN AND STUDENTS’ WORKSHEET BY APPLYING INQUIRY-BASED LEARNING IN TEACHING RECOUNT TEXTS FOR THE FIRST YEAR STUDENTS OF SMA - Amira Hafizah Putri Elham; Atni Prawati; Mahdum Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is aimed at developing English instructional tools (lesson plan and students’ worksheet) by applying inquiry-based learning as one of the learning model suggested in the 2013 curriculum and to find out the validity level of developing English lesson plan and students’ worksheet by applying inquiry-based learning in teaching recount texts for the first year students of SMA. This research is a developmental research using 4-D Model by Thiagarajan (1974). To develop lesson plan and students’, there were three stages involve in this research, (a) define stage which is done to collecting various information relating to the product to be developed., (b) design stage which is done to plan the draft of instructional tools and arranged it into the right format and (c) develop stage which is done to validate and try-out the instructional tools. In order to find out the validity level of developing instructional tools, the data were collected using validation sheet of lesson plan, validation sheet of students’ worksheet validated by experts and students response questionnaire. Based on data analysis result, the validation score of lesson plan is 95,14% and the validation score of students’ worksheet is 93,56% and the average score of students’ response is 96,36%. The result showed that the instructional tools in the form of lesson plan and students’ worksheet were very valid and can be implemented for the first year students of SMA.Key Words: Developing, Lesson Plan, Students’ Worksheet, Inquiry-Based Learning, Recount Texts